Strengthening the Corporate Social Responsibility Reporting in Indonesia - Dhiafira, Alma Putri (Center for Law and Responsible Business Studies, 2026)
Integrating sustainable development into corporate operations has become increasingly important, as business activities significantly affect both society and the environment. In Indonesia, Corporate Social Responsibility (CSR) has transitioned from a voluntary initiative to a legal obligation designed to address sustainability challenges. The government has made ongoing efforts to improve the regulatory framework to ensure CSR contributes more effectively to sustainable development, drawing lessons from international models that have shifted from soft law approaches toward binding obligations. Companies are required to report their CSR activities through the Investment Activities Report or the Laporan Kegiatan Penanaman Modal (LKPM), which serves as a key mechanism for transparency and accountability. This paper analyses how Indonesia can strengthen CSR implementation by improving the LKPM reporting process. By examining the evolution of CSR regulation in the United Kingdom (UK) and Europe, it identifies strategies to enhance Indonesia’s CSR system in terms of accountability, transparency, and its overall impact on sustainable development.